How Should Tobacco Be Taxed in EU-Accession Countries? - Sijbren Cnossen (Center for Economic Studies and ifo Institute (CESifo), 2001)
Ten Central and Eastern European countries, as well as Cyprus and Malta, have applied for membership of the European Union. Membership involves, among others, alignment of the taxes on tobacco products. Within the acquis communautaire, accession countries can choose between a predominantly specific and a predominantly ad valorem excise regime. The choice affectsrevenue, tobacco consumption control, and EU competition. Thispaper examines the arguments and concludes that a predominantlyspecific regime seems to be the preferred choice.
Keywords: 330